2019
DOI: 10.1002/ijc.32125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of induction therapy with lenalidomide, doxorubicin and dexamethasone on bone remodeling and angiogenesis in newly diagnosed multiple myeloma

Abstract: There is limited data regarding the efficacy and safety of lenalidomide, adriamycin and dexamethasone (RAD) combination on newly diagnosed multiple myeloma (NDMM) patients. There is also scarce information about the effect of lenalidomide on bone metabolism and angiogenesis in NDMM. Thus, we conducted a Phase 2 study to evaluate the efficacy and safety of RAD regimen as induction in transplant‐eligible NDMM patients and we studied the effects on bone metabolism and angiogenesis. A total of 45 patients were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Parathyroid hormone-related protein (PTHrP) is usually within normal limits in contrary with solid tumors and myeloma patients usually respond rapidly to corticosteroids administration, due to rapid control of the disease. Interestingly, anti-myeloma treatment seems to restore bone metabolism [ 95 , 96 , 97 , 98 , 99 ], whereas anti-resorptive treatment such as bisphosphonates and anti-RANKL agents reverse myeloma-induced hypercalcemia [ 90 , 96 ].…”
Section: Metabolic Disturbances Of Calcium Metabolismmentioning
confidence: 99%
“…Parathyroid hormone-related protein (PTHrP) is usually within normal limits in contrary with solid tumors and myeloma patients usually respond rapidly to corticosteroids administration, due to rapid control of the disease. Interestingly, anti-myeloma treatment seems to restore bone metabolism [ 95 , 96 , 97 , 98 , 99 ], whereas anti-resorptive treatment such as bisphosphonates and anti-RANKL agents reverse myeloma-induced hypercalcemia [ 90 , 96 ].…”
Section: Metabolic Disturbances Of Calcium Metabolismmentioning
confidence: 99%
“…Bisphosphonates, especially zoledronic acid, and denosumab, a monoclonal antibody binding to the receptor activator of nuclear factor kappa-Β ligand (RANKL), are the mainstay of treatment for MM-related bone disease [ 3 ]. Furthermore, anti-myeloma drugs, such as the proteasome inhibitors bortezomib and carfilzomib, have shown a positive effect on bone health [ 4 , 5 , 6 , 7 , 8 ]. Consequently, research into agents that combine anti-myeloma activity with positive effects on bone metabolism is of high importance [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high failure rate of stem cell mobilization in the RAD group also led to difficulty with ASCT and hematopoietic reconstitution, which was the major reason for treatment interruption. However, in the study by Terpos et al, 9 89% of patients successfully mobilized stem cells after four courses of RAD induction, and the average number of CD34+ cells collected was 8.94 × 10 6 /kg. In addition, Baz et al 8 reported that in 31 T A B L E 4 Stem cell mobilization, transplantation, and hematopoietic reconstruction patients with MM induced by the RAD regimen for four to eight courses, the number of stem cells collected from all of the patients was ≥2 × 10 6 /kg.…”
Section: Discussionmentioning
confidence: 91%
“…Baz et al 8 reported that the RAD regimen resulted in a 77.2% overall response rate (ORR) in NDMM patients. In addition, Terpos et al 9 found that the ORR was 66.7% after four cycles of RAD induction. However, all of these trials were single‐arm phase II trials, and the regimens were not compared with other induction regimens.…”
Section: Introductionmentioning
confidence: 98%